Association between non-alcoholic fatty liver disease and chronic plaque psoriasis: Deep to the skin: Psoriasis and fatty liver disease - Fahim, Muhammad; Khoso, Hina; Noor, Sahibzada Mahmmod; Naeem, Muhammad; Bakhtiar, Rabeeka (Journal of Pakistan Association of Dermatologists, 2023)
Objective To compare the frequency of Non-Alcoholic Fatty Liver Disease (NAFLD) in psoriasis patients (cases) with. non-psoriasis patients (controls) and to stratify it with respect to various independent variables in both groups. Methods It was a case-control study done at the Dermatology department, Lady Reading Hospital, Peshawar, with a total of 160 participants and 80 in each group. NAFDL was diagnosed with the help of abdominal ultrasound and considered relevant only after other secondary causes of NAFLD (as mentioned in exclusion criteria) were excluded. Results The mean age in cases and controls was 36±4.77 years and 40±13.12 years respectively. The cases included 59 % male and 41% female while controls groups consisted of 51% female and 49% male patients. In Cases group, 30 patients (37.5%) had NAFLD while in Controls 16 patients (20%) patients had NAFLD disease, with p-valve =0.0144). Conclusion Our study concludes that there is a positive association between chronic plaque psoriasis with NAFLD compared with age, gender, and body mass index (BMI)-matched non-psoriasis.